On some definite integrals connecting with sums related to inverse tangent function - Ramesh Kumar Muthumalai (Scientia Series A: Mathematical Sciences, 2025)
Some definite integrals are evaluated through sums related to inverse tangent function that found in chapter 2 of Ramanujan notebooks, Part-I. In addition, integrals involving complicated arguments of inverse tangent function are evaluated through in nite products.
Keywords: Definite integrals; infinite products; inverse tangent function; Ramanujan notebooks